Recirculating aquaculture systems waste water as a medium for increase of phytoplankton and zooplankton biomass - Чебан, Лариса (My University, 2016)
The results of using the waste water from recirculating aquaculture system for phytoand zooplankton cultivation are presented in the article. The physico-chemical parameters of the aquaculture system’s waste water and comparative culture media were recorded during hydrobionts cultivation. The indicators of productivity and the biochemical composition of investigated cultures were determined. The biochemical analysis of studied cultures included the investigations of the content of total proteins, lipids, carbohydrates, carotenoids and photosynthetic pigments. Using aquaculture system’s waste water as a medium for the cultivation of phyto- and zooplankton can significantly reduce the cost of technology for live feed biomass increase in the aquaculture industries.
Keywords: live feed for fish; waste water; RAS; cultivation; phytoplankton; nutritional value; zooplankton